ANALYSIS OF RENEWABLE ENERGY RESOURCES FROM REGIONAL DEVELOPMENT IN EASTERN ANATOLIA REGION EXAMPLE - Kanberoglu, Zafer; Polat, İbrahim Halil (International Journal of Contemporary Economics and Administrative Sciences, 2018)
One of the most fundamental problems of today’s economies is regional development differences. One of the most important instruments for eleminating developmental differences is energy sources. Energy resources are divided into two parts, nonrenewable and renewable. The danger of extinction in sources like non-renewable energy sources such as oil and natural gas has led economic structures to concentrate on renewable energy sources such as wind and solar. In this context, renewable energy sources have become important both in macro and regional development. In this study, the role of renewable energy resources in regional development has been analyzed in the case of Eastern anatolia region. The empirical findings of the study show that both Turkey and the Eastern anatolia region have significant potential in terms of renewable energy sources, but that they do not make enough use of energy resources.